Recent Advancements and Applications of Human Immune System Mice in Preclinical Immuno-Oncology. (February 2020) - Curran, Michelle; Mairesse, Maelle; Matas-Céspedes, Alba; Bareham, Bethany; Pellegrini, Giovanni; Liaunardy, Ardi; Powell, Edward; Sargeant, Rebecca; Cuomo, Emanuela; Stebbings, Richard; Betts, Catherine J.; Saeb-Parsy, Kourosh
Significant advances in immunotherapies have resulted in the increasing need of predictive preclinical models to improve immunotherapeutic drug development, treatment combination, and to prevent or minimize toxicity in clinical trials. Immunodeficient mice reconstituted with human immune system (HIS), termed humanized mice or HIS mice, permit detailed analysis of human immune biology, development, and function. Although this model constitutes a great translational model, some aspects need to be improved as the incomplete engraftment of immune cells, graft versus host disease and the lack of human cytokines and growth factors. In this review, we discuss current HIS platforms, their pathology, and recent advances in their development to improve the quality of human immune cell reconstitution. We also highlight new technologies that can be used to better understand these models and how improved characterization is needed for their application in immuno-oncology safety, efficacy, and new modalities therapy development.